2017
DOI: 10.17060/ijodaep.2017.n1.v3.1013
|View full text |Cite
|
Sign up to set email alerts
|

Nuevos Recursos Tecnológicos Para Trabajar en Un Aula De Educación Infantil: El Cuento Interactivo Considerado Un Recurso De Aprendizaje

Abstract: RESUMENActualmente, las nuevas Tecnologías de la Información y Comunicación (TIC) se consideran un recurso clave para la enseñanza, de tal manera que este concepto está evolucionando y tenemos un nuevo término: TAC (Tecnologías del Aprendizaje y la Comunicación). Esta comunicación analiza algunos de los recursos que pueden ser utilizados e integrados en aulas de Educación Infantil, en concreto los cuentos interactivos, ya que según la normativa actualdebemos introducirlas durante esta etapa. Con el fin de inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…The first factor, "characteristics of the digital stories", encompassed aspects related to the characteristics of the digital stories, considering that it dealt with a fundamental educational tool that entails a medium for the transmission of beliefs and values that has a character of entertainment, and which promotes creativity, the making of decision, conflict resolution, and personal autonomy, aside from helping in the achievement of objectives and the contents of the curriculum [9,10,28,30]. All of these characteristics, found in the first factor, refer to previous scientific studies, which analyzed the characteristics and the potential of digital stories [4,5,20,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first factor, "characteristics of the digital stories", encompassed aspects related to the characteristics of the digital stories, considering that it dealt with a fundamental educational tool that entails a medium for the transmission of beliefs and values that has a character of entertainment, and which promotes creativity, the making of decision, conflict resolution, and personal autonomy, aside from helping in the achievement of objectives and the contents of the curriculum [9,10,28,30]. All of these characteristics, found in the first factor, refer to previous scientific studies, which analyzed the characteristics and the potential of digital stories [4,5,20,29].…”
Section: Discussionmentioning
confidence: 99%
“…Based on what has been previously described, the main objective of the present work has been achieved, as the instrument that focused on the creation of digital stories through the use of free software (Utellstory) has been confirmed and validated. This allows us to provide a significant advance for the development of reliable measurements or instruments for the design, creation, and production of digital stories, given the present lack of validation studies that confirm the dimensional structure or the construct related to the creation of digital stories and the didactic possibilities they bring, as most of the studies are qualitative in character [20,30,47]. Therefore, it can be concluded that this study represents a benchmark contribution to the study of the phenomenon and the development and validation of a scale about digital stories in Spain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuando con los aspectos digitales, Domínguez et al (2017) demuestran la vigencia y utilidad de este soporte. Estos últimos destacaban particularmente el paso de las nuevas Tecnologías de la Información y Comunicación (TIC) a las Tecnologías del Aprendizaje y la Comunicación (TAC) en relación con proyectos de libros infantiles interactivos.…”
Section: Introductionunclassified
“…Por todo esto, la presente investigación tiene como objetivo fundamental fomentar en los docentes la utilización de recursos tecnológicos didácticos e innovadores para optimizar y enriquecer el proceso de enseñanza-aprendizaje del área de matemática, en básica superior, mediante el empleo de prácticas innovadoras mediadas por las TIC, actualmente resulta fundamental dotar a los docentes de nuevas estrategias y competencias tecnológicas, que les permita dejar atrás la enseñanza tradicional, se innoven y estén acorde a las exigencias del mundo actual del hoy (Domínguez, et al, 2017).…”
Section: Introductionunclassified